Common agricultural policy instruments as factors of environmental sustainable development of Polish agricult - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2013)
The Paper's goal is the identification of the Common Agricultural Policy (CAP) instruments as factors influencing environmental sustainable development of Polish agriculture. These instruments were assessed in the light of the way in which agricultural and environmental policies are projected and introduced. Direct payments - on one hand - contribute to intensification of agriculture (causing negative environmental externalities). On the other hand,- they are important factors of maintenance of extensive farms in other regions (enabling environmental services delivery). The environmental impact of the CAP is strictly associated with cross-compliance. However, Polish authorities did not implement many important standards (regarding water protection, biodiversity and soil conservation). The agri-environmental programme is a factor with a strong positive impact on sustainable development. However, in Poland, its effectiveness of its financing is relatively low - especially in comparison to the main groups of the EU member states. Other CAP instruments with potential positive influence on sustainable development (supporting the development of less favourite areas, afforestation programmes) were insufficiently directed to stimulate supply of environmental services.
Keywords: 330; sustainable agriculture; rural development; sustainable agriculture development; environment protection in agriculture; rural development measures; agri-environmental programme